FLEXURAL IMPROVEMENT OF PLAIN CONCRETE BEAMS STRENGTHENED WITH HIGH PERFORMANCE FIBRE REINFORCED CONCRETE (Nigerian Journal of Technology, 2017)
Strengthening of concrete structures have become inevitable due to unavoidable factors such as fatigue and aggressive environmental conditions causing deterioration of concrete structures. Many researchers have turned in the direction of using various high strength and high performance concretes due to their high structural and durability properties, for the purpose of repair and strengthening of concrete structures against these aggressive conditions. As a result, this study carryout experimental, numerical and analytical investigation to study the behaviour of plain concrete (PC) beams strengthened with High Performance Fibre Reinforced Concrete (HPFRC) layer using three different jacketing configurations and tested in flexure. Results show significant improvement in both stiffness and load bearing capacity of plain concrete beams. http://dx.doi.org/10.4314/njt.v36i3.6